Vulnerability of the karst area related to potentially toxic elements - Hana Fajković; Ozren Hasan; Slobodan Miko; Mladen Juračić; Saša Mesić; Esad Prohić (Geologia Croatica, 2011)
Soil samples from 31 locations in the Una river spring catchment were subject to chemical extraction analyses. The data were presented as distribution maps of potentially toxic elements (Al, Cu, Mn, Pb and Zn) in the surface soil of the area. To evaluate the vulnerability of the immediate spring zone of the karst catchment, the vulnerability map was derived from the application of the PI methodology proposed by the European COST Action 620. The PI method used to produce the vulnerability map takes into account the protective cover (P) and the infiltration conditions (I). It is based on the origin-pathway-target model. The π-factor (π = P ´ I) describes the vulnerability in the area, subdivided into 5 classes: π-factor in the range 0-1 implies an area of extreme vulnerability, while π-factor in the range 4-5 implies an area of very low vulnerability. The extraction procedure for the elements Al, Cu, Mn, Pb and Zn, has been applied in order to determine the potential mobility and redistribution of elements that could influence the groundwater and affect its quality. The applied extraction was the second step of the sequential procedure proposed by TESSIER et al. (1979), i.e. extraction with 1 mol dm-3 CH3COONa/CH3COOH buffer (pH 5). The results provide information on the potential mobility of the studied elements, indicating the possibility of their mobilization through changes in pH. Lead shows the greatest amount of mobility, with a mean of 9% (max. 16%) extracted under an acidic condition. Manganese follows with a mean of 5% (max. 11%) and zinc, copper and aluminium show less than 1% (mean) mobility. The vulnerability map of the karst area was produced in order to predict potential problem areas of karst aquifers. The Una spring catchment area presents generally low to moderate vulnerability; 8% of the studied area can be considered as extremely vulnerable according to the PI-methodology. Based on these data it was possible to delineate areas with a low protection cover i.e. combining the vulnerability map of the karst area with the distribution maps of potentially toxic elements, areas considered extremely vulnerable could be identified.